Not for Profit - Veldhuis, Ruud (JSSE - Journal of Social Science Education, 2011)
In this book Nussbaum makes a strong case for the importance of the liberal arts in education. If the economic pressure of globalization is not kept under control, the end result might be an erosion of our democracies. The book is more a manifesto (178 pages) and not an empirical study. Quantitative data have been omitted.